Spectroscopic Discrimination of Diastereomeric Complexes Involving an Axially Chiral Receptor. Issue 18 (7th August 2017) - Filippi, Antonello; Fraschetti, Caterina; Guarcini, Laura; Zazza, Costantino; Ema, Tadashi; Speranza, Maurizio
Abstract: The infrared multiphoton dissociation (IRMPD) spectra of electrospray ionization (ESI)‐formed proton‐bound complexes between the axially chiral multifunctional macrocycleM aR andd ‐ andl ‐phenylalanine (P D andP L ) ord ‐ andl ‐3, 4‐dihydroxyphenylalanine (D D andD L ) are recorded in the ν ˜ =2800–3700 cm −1 region. Whereas the diastereomeric [M aR ⋅ H⋅P D ] + and [M aR ⋅ H⋅P L ] + complexes do not show any significant spectral differences, the spectrum of [M aR ⋅ H⋅D D ] + clearly diverges from that of its [M aR ⋅ H⋅D L ] + diastereomer. A comparison of the experimental spectra with the B3LYP/6‐31G**‐calculated harmonic vibrational frequencies of a number of stable structures indicates the formation, in the ESI source, of very similar spectroscopically active structures, with the protonated amino acid placed outside the flat cavity of the macrocycle and hydrogen‐bonded at its O2 center. Different spectral signatures of the [M aR ⋅ H⋅D D ] + and [M aR ⋅ H⋅D L ] + complexes are attributed to the coexistence of several stable rotamers in the ESI source. Abstract : A rare spectral vision : The infrared multiphoton dissociation (IRMPD) spectra of electrospray ionization (ESI)‐formed proton‐bound complexes between an axially chiral macrocycle and the enantiomers of different amino acids agree with IR‐active structures in which the N‐protonated amino acid is hydrogen‐bonded to the O2 center of the receptor. Different IRMPD signatures are explained by the coexistence of many rotamers in the ESI source (see figure; dopa=3, 4‐dihydroxyphenylalanine).